Protein disulphide isomerase-mediated LA419– NO release provides additional antithrombotic effects to the blockade of the ADP receptor - Vilahur, Gemma; Pena, Esther; Padró, Teresa; Badimon, Lina (Thrombosis and Haemostasis, 2007)
Despite the proven efficacy of current antithrombotic therapy in preventing ischemic heart disease (IHD), vascular events still occur. Our aims were i) to evaluate if combined oral treatment of clopidogrel and LA419, a novel nitric oxide donor with antiischemic and antiplatelet properties, provides additional antiplatelet effects to those of the blockade of P2Y12 receptor; and ii) to gain insight into the mechanism behind LA419 antiplatelet effects. Pigs (n=16) were randomized into four groups: 1) placebocontrol; 2) LA419; 3) clopidogrel; and 4) LA419+clopidogrel. Both compounds were administered orally: LA419 0.9 mg kg-1 twice daily for 10 days; clopidogrel 10 mg kg-1 day the three last days. Antithrombotic effects were assessed by measuring platelet deposition (PD) triggered by denuded and disrupted vessel wall placed on the Badimon chamber. LA419 effects on platelet aggregation, hemodynamic parameters, and platelet protein expression upon in vitro thrombin stimulation were also evaluated. Total PD on denuded vessels was similarly reduced by all treatments with respect to placebo (p<0.05). However, combination of LA419+clopidogrel largely reduced PD triggered by disrupted vessel wall by 80% versus placebo (p<0.005), 15% versus clopidogrel alone (p<0.01), and 30% versus LA419 alone (p<0.005). All treatments inhibited collagen- and ADP-induced platelet aggregation, and no variations were detected in hemodynamic parameters. Proteomic analysis revealed that LA419 was associated with an increase in membrane protein disulphide isomerase (protein implicated in nitric oxide release).Treatment with LA419 may result in additional antiplatelet effect to that of clopidogrel in addition to restoring impaired endothelial dependent vasodilation without hemodynamic side effects. Further studies in IHD patients seem warranted.
Keywords: Thrombosis; platelets; nitric; oxide